Factors Influencing Proper Healthcare Waste Management Practices Among Healthcare Workers in Nigeria - Umaru, Isaac John; Asare, Solomon Ossom; Morgan, Akpan Usenobong; Umogbai, Debora Akinola; Chukwudi, Emmanuel Eluu; Essien, Inemesit Samuel; Olayemi, Abimbola Gbenga; John, Omachi Blessing (Darul Yasin Al Sys, 2025)
Healthcare waste management (HCWM) is a critical component of public health and environmental safety, particularly in developing countries like Nigeria where improper disposal practices pose significant risks, and compliance among healthcare workers remains inconsistent despite the existence of national guidelines and global protocols. This study aimed to assess the factors influencing proper HCWM practices among healthcare workers in Nigeria, focusing on knowledge, attitudes, institutional support, and policy awareness. A cross-sectional survey was conducted among 300 healthcare workers across tertiary and secondary health facilities in Abuja, Lagos, and Kano. Data were collected using structured questionnaires covering demographic information, HCWM knowledge, attitudes, practices, and institutional factors, and were analyzed in SPSS v25 using chi-square tests and logistic regression to identify significant predictors of compliance. Among the respondents, 60% had received formal HCWM training, 70% were aware of HCWM guidelines, and 75% expressed positive attitudes toward waste management; however, only 55% practiced correct waste segregation and 50% reported adequate institutional support. Chi-square analysis revealed significant associations between HCWM training and proper waste segregation (χ² = 12.45, p < 0.01), and between institutional support and PPE usage (χ² = 9.78, p < 0.05). Logistic regression identified HCWM training (OR = 2.3, 95% CI: 1.5–3.6) and positive attitude (OR = 1.8, 95% CI: 1.2–2.9) as significant predictors of proper HCWM practices. The study concludes that training, institutional support, and attitudes are key determinants of HCWM compliance among healthcare workers in Nigeria, and that bridging the gap between knowledge and practice requires targeted interventions, infrastructure investment, and policy enforcement. Strengthening HCWM systems is essential for reducing occupational hazards, preventing environmental contamination, and promoting sustainable healthcare delivery.